Geochemistry indices and biotests as useful tools in the assessment of the degree of sediment contamination by metals - Koniarz, Tomasz; Tarnawski, Marek; Baran, Agnieszka (Geology, Geophysics and Environment, 2023)
Ecological and geochemical indicators have been widely accepted as tools with the potential for rapid risk assessment of metal contamination of bottom sediments. In this study, we propose a selection of such indicators to characterize the potential ecological risks stemming from metal contamination of the bottom sediments of the Chechło reservoir (S Poland). The Chechło reservoir is located in an area formerly occupied by zinc and lead ore mining and processing industry. High amounts of metals, especially zinc (39.37–4772.00 mg/kg d.m.), cadmium (0.37–21.13 mg/kg d.m.) and lead (4.50–434.49 mg/kg d.m.) have been found in the bottom sediments. Both geochemical (CD – contamination degree) and ecological indices (mean PECQ) were indicative of bottom sediment contamination and their potential toxicity to living organisms. Most of the bottom sediment samples (71%) examined were toxic for Heterocypris incongruens, while only 9% of the samples were toxic to Sinapis alba. However, no significant correlations between the metal content and the response of the test organisms were observed. Correlation and principal component analyses (PCA) showed that silt and clay fractions were the key factors influencing the metal content in the sediments. Our study makes a contribution to building evidence of the need to integrate several indices for the assessment of environmental risks related to the presence of metals in bottom sediments rather than relying on a single one.